EGF receptor modulates HEV entry in human hepatocytes - Haase, Jil Alexandra; Burkard, Thomas L.; Brüggemann, Yannick; Gömer, André; Meister, Toni L.; Fu, Rebecca Menhua; Mehnert, Ann-Kathrin; Dao Thi, Viet Loan; Behrendt, Patrick; Durantel, David; Broering, Ruth; Vondran, Florian W. R.; et al. (Hepatology, 2023)
Being the most common cause of acute viral hepatitis with >20 million cases per year and 70,000 deaths annually, HEV presents a long-neglected and underinvestigated health burden. Although the entry process of viral particles is an attractive target for pharmacological intervention, druggable host factors to restrict HEV entry have not been identified so far. ...